Quantification of BRIS Soil Bacteria at Tembila, Besut Terengganu - Zakiah Mustapha; Nashriyah Mat; Radziah Othman; Abd Jamil Zakaria (AGRIVITA, Journal of Agricultural Science, 2017)
A study was made to determine total number of bacteria living in the rhizosphere of three common plants at BRIS soil namely Acacia mangium, Melaleuca cajuputi Powell and Eleusine indica that grow on field. Soil samples were collected from each plant’s rhizosphere at three different locations of UniSZA Apiary, AGROPOLIS Research Farm and FBIM Teaching Farm at UniSZA, Besut Campus on May and November 2015. Enumeration of total bacteria by standard plate counts found that Acacia’s rhizosphere at AGROPOLIS Research Farm showed the highest CFU g-1 in November 2015 for aerobic (6.14 x 106) and anaerobic (3.97 x 106) bacteria. Acacia’s rhizosphere from UniSZA Apiary showed the highest CFU g-1 value in November 2015 for nitrogen fixing bacteria (aerobic; 1.87 x 106, anaerobic; 1.5 x 106) and phosphate solubilization bacteria (aerobic; 1.4 x 106, anaerobic; 1.41 x 106). The rainy season on November gave a higher bacterial CFU g-1 number (20-44 %) compared to the dry season on May for all different plants and locations. The finding showed that although BRIS soil is the problematic and unfertile soil, it has a large number of bacterial colony that might be beneficial to be exploited for enhancing plant growth and soil fertility.